2008
DOI: 10.1127/0941-2948/2008/0284
|View full text |Cite
|
Sign up to set email alerts
|

On the reduction of urban particle concentration by vegetation a review

Abstract: In order to assess the filtration performance of plants with respect to atmospheric dust, deposition on vegetation has been investigated by a number of different methods (field studies, numerical and physical modelling) over the past few years. The intention of this review is to assess the extent to which a reduction in particle concentration (especially PM 10) can be accomplished by existing vegetation or targeted planting on the basis of international publications. The range of this assessment however is lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
154
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(160 citation statements)
references
References 25 publications
5
154
0
1
Order By: Relevance
“…Roadside tree canopies may adjust air quality through changing air dispersion as well as by capturing air pollutants. Recent studies have found that a street tree canopy has a positive or negative effect on air quality at the pedestrian level [37,38]. The positive effect is the obstacle posed by plants to air flow, reducing air exchange especially in the vertical direction and increasing air pollutant concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Roadside tree canopies may adjust air quality through changing air dispersion as well as by capturing air pollutants. Recent studies have found that a street tree canopy has a positive or negative effect on air quality at the pedestrian level [37,38]. The positive effect is the obstacle posed by plants to air flow, reducing air exchange especially in the vertical direction and increasing air pollutant concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…For green streets within street canyons, designers may want to limit the number of trees in bioretention cells and suspended pavement systems and focus on using stormwater measures based on herbaceous vegetation (e.g., bio-retention cells and bio-swales). The close proximity of the vegetation to the PM 10 emission sources maximizes the efficiency of interception and deposition; also, the smaller size of vegetation in installations such as street gardens does not significantly hinder air flow within the street [42].…”
Section: Green Streets: Pollutant Trapping Benefitsmentioning
confidence: 99%
“…As resuspension decreases rapidly with time after deposition, it is normally already included in measured velocities. In modelling, it is also normal practice to integrate re-suspension into the deposition velocity (Litschke and Kuttler 2008). A vegetative cover could reduce re-suspension of soil material or previously deposited atmospheric particles due to reduced wind speeds in canopies and to the fixation of particles by roots (Langner 2008).…”
Section: Reducing Re-suspensionmentioning
confidence: 99%
“…Trees may mitigate the damaging effects of airborne particles through removal and subsequent lowering of concentrations (Beckett et al 2000, Litschke and Kuttler 2008, Prajapati 2012, Schaubroeck et al 2014). Farmer (1993 reported that trees are biological filters for airborne particles due to their large leaf surfaces relative to ground covered.…”
Section: Effectiveness Of Tree Cover In Reducing Airborne Pollutionmentioning
confidence: 99%
See 1 more Smart Citation